Classroom Gems : Games Ideas and Activit: Games, Ideas and Activities for Primary Drama - Theodorou, Michael (New Dehli Pearson, 2014)
Description The book aims to provide ready-made drama lesson ideas, in the three key areas of movement, voice and character. These activities will considerably reduce the workload for many overburdened teachers, and can be easily adapted to suit varying levels of ability. Offering links to many curriculum areas, this resource will provide a strong base of accessible ideas to enhance drama education in the primary classroom. The companion website to accompany the book will offer unique scripted scenes from great literary works which will offer the teacher further ideas for not just one lesson, but a series of lessons, as well as a 'Teachers Notes' section. An essential tool to help bring creativity to life in the classroom!
Include Illustrations
Keywords: Primary Drama